Encyclopedia of Polymer Science and Technology 2016
DOI: 10.1002/0471440264.pst648
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide‐Mediated Polymerization

Abstract: Nitroxide‐mediated polymerization (NMP) has been studied abundantly in the past three decades. There are several very good and recent reviews on the topic available in the literature. Although in this article we provide an overview on the research efforts focused on the polymer chemistry of NMP, our emphasis is placed on research aspects of NMP from a polymer reaction engineering perspective. Namely, we emphasize the use of engineering tools (such as mathematical modeling) on the design, analysis, and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 247 publications
0
8
0
Order By: Relevance
“…The controlled synthesis of polymers by the nitroxide-mediated reversible inhibition method was actively developed for almost three decades. This direction became not only the “versatile lab tool” of synthetic chemists making it possible to synthesize polymers with desired properties but it went on “industrial rails.” The application of this method in the manufacture of adhesives, coatings, dispersers, and compatibilizers is expanding [ 94 ]. Therefore, the problems of green chemistry are very urgent and important for the specified processes, although special attention has been given to them only in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…The controlled synthesis of polymers by the nitroxide-mediated reversible inhibition method was actively developed for almost three decades. This direction became not only the “versatile lab tool” of synthetic chemists making it possible to synthesize polymers with desired properties but it went on “industrial rails.” The application of this method in the manufacture of adhesives, coatings, dispersers, and compatibilizers is expanding [ 94 ]. Therefore, the problems of green chemistry are very urgent and important for the specified processes, although special attention has been given to them only in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…The main RDRP techniques, namely, nitroxide-mediated polymerization (NMP) [ 11 , 12 ], atom transfer radical polymerization (ATRP) [ 13 ], and reversible addition-fragmentation chain transfer polymerization [ 14 ], have allowed the synthesis of functional polymers with predefined molar masses, low dispersity values, and defined microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Nitroxide-mediated radical polymerization (NMP), a type of reversible deactivation radical polymerization (RDRP) technique, has been successfully applied to the synthesis of polymers with narrow molar mass distributions, covering an extensive range of reaction conditions. Both academic and industrial sectors have shown great interest in RDRP processes because of their potential to produce well-defined polymeric materials with low molar mass dispersities ( Đ ) and controlled microstructures, for a range of monomers, and important potential applications . RDRP techniques combine the best features of conventional free radical polymerization (FRP), such as tolerance to impurities and water, a variety of easily attainable reaction conditions, types of industrial processes, and a range of monomers, with those of living polymerization (LP) (anionic or cationic), such as efficient control of the microstructures and architectures of vinyl polymers . The other two most widely used RDRP techniques are atom transfer radical polymerization (ATRP) and reversible addition–fragmentation chain transfer (RAFT) polymerization. , Additional RDRP techniques include iodine-mediated polymerization , and polymerizations with N -hydroxyphthalimide (NHPI) and xanthone redox initiation. , …”
Section: Introductionmentioning
confidence: 99%